Konsep Tri Pusat dalam Pendidikan Sekolah Berbasis Pesantren: Memperkuat Dimensi Spiritual, Akademik, dan Sosial - Muhamad Slamet Yahya (Jurnal Kependidikan, 2022)
This study aims to evaluate the implementation of the Tri Pusat concept in pesantren education at SMK Ma’arif 6 Kebumen and examine its contribution to strengthening the spiritual, academic, and social dimensions of students. A qualitative approach was employed, involving classroom observations, interviews, and document analysis. The findings indicate that SMK Ma’arif 6 Kebumen has successfully implemented the Tri Pusat concept holistically. The spiritual dimension is reinforced through religious instruction and regular religious practices. The academic dimension is emphasized through a comprehensive curriculum and practical learning. Meanwhile, the social dimension is developed through extracurricular activities and community service. The implementation of the Tri Pusat concept benefits students in their spiritual, academic, and social development. Despite challenges in implementation, continuous efforts are made to improve its effectiveness. In conclusion, the implementation of the Tri Pusat concept at SMK Ma’arif 6 Kebumen makes a positive contribution to strengthening the spiritual, academic, and social dimensions of students.